Expectations hypothesis in the Cetes market in Mexico: 1990-1995 - Galindo, Luis M. (Estudios Económicos de El Colegio de México, 1995)
The objective of this essay is to analyze the expectations hypothesis under the assumption of rational expectations for the public bond market in Mexico. The results indicate that the expectations hypothesis with rational expectations is rejected. The empirical evidence also indicates that there is a stable long term relationship between short and long term interest rates and that the term structure and the changes in the short term interest rates contain information with which future changes in interest rates can be forecasted.